2002
DOI: 10.1016/s0896-6273(02)00790-0
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Muscarinic Modulation of M Current Channels Requires Phosphatidylinositol 4,5-Bisphosphate Synthesis

Abstract: Suppression of M current channels by muscarinic receptors enhances neuronal excitability. Little is known about the molecular mechanism of this inhibition except the requirement for a specific G protein and the involvement of an unidentified diffusible second messenger. We demonstrate here that intracellular ATP is required for recovery of KCNQ2/KCNQ3 current from muscarinic suppression, with an EC(50) of approximately 0.5 mM. Substitution of nonhydrolyzable ATP analogs for ATP slowed or prevented recovery. AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
482
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(517 citation statements)
references
References 53 publications
32
482
3
Order By: Relevance
“…Activation of GIRK channels requires permissive levels of membrane PIP 2 and increased channel activity results from Gβγ-mediated stabilization of PIP 2 -GIRK binding (Huang et al, 1998, Zhang et al, 1999. In fact, the regulation of channel activities by Gβγ, PIP 2 , or phosphorylation occurs on the time scale of a few seconds which can be resolved by electrophysiological techniques (Suh and Hille, 2002). In recent studies from our lab we have found that PI3K plays a critical role in facilitating the rapid membrane response to estrogen, as elucidated by the use of PI3K inhibitors (Malyala et al, 2008).…”
Section: Effects Of 17β -Estradiol On Vmh and Arcuate Neurons: Role Imentioning
confidence: 99%
“…Activation of GIRK channels requires permissive levels of membrane PIP 2 and increased channel activity results from Gβγ-mediated stabilization of PIP 2 -GIRK binding (Huang et al, 1998, Zhang et al, 1999. In fact, the regulation of channel activities by Gβγ, PIP 2 , or phosphorylation occurs on the time scale of a few seconds which can be resolved by electrophysiological techniques (Suh and Hille, 2002). In recent studies from our lab we have found that PI3K plays a critical role in facilitating the rapid membrane response to estrogen, as elucidated by the use of PI3K inhibitors (Malyala et al, 2008).…”
Section: Effects Of 17β -Estradiol On Vmh and Arcuate Neurons: Role Imentioning
confidence: 99%
“…Muscarinic agonists inhibit this channel via a G q -coupled pathway that evokes phosphoinositide turnover 20,21 (Fig. 6a).…”
Section: Akap150 Coordinates Muscarinic Suppression Of M Currentsmentioning
confidence: 99%
“…First, Li þ inhibits several cellular enzymes involved in inositol recycling, a crucial step in the synthesis of the PIP2, 43 a membrane phospholipid that is essential for KCNQ2 activity and for its regulation by acetylcholine as well as by other neurotransmitters and peptides. [44][45][46] Li þ by interfering with this pathway of regulation will necessarily interfere with KCNQ2 activity either basic or regulated by neurotransmitters such as acetylcholine acting on the M1 receptor. Second, the kinase GSK3b has also been shown to be inhibited by Li þ 43,47 and we have shown in this paper that GSK3b can, in vitro, phosphorylate KCNQ2 and that this phosphorylation is decreased by Li þ .…”
Section: Pp2a-bc and Kcnq2 In Bipolar Diseasementioning
confidence: 99%